Assessing the impact of an evidence- and consensus-based guideline for controlling SARS-CoV-2 transmission in German schools on decision-making processes: a multi-component qualitative analysis - Katharina Wabnitz; Mike Rueb; Eva A. Rehfuess; Brigitte Strahwald; Lisa M. Pfadenhauer (Health Research Policy and Systems)
Abstract Introduction During the COVID-19 pandemic, decision-making on measures to reduce or prevent transmission of SARS-CoV-2 in schools was rendered difficult by a rapidly evolving and uncertain evidence base regarding their effectiveness and unintended consequences. To support decision-makers, an interdisciplinary panel of scientific experts, public health and school authorities as well as those directly affected by school measures, was convened in an unprecedented effort to develop an evidence- and consensus-based public health guideline for German schools. This study sought to assess whether and how this guideline impacted decision-making processes. Methods This study comprised three components: (1) we sent inquiries according to the Freedom of Information Acts of each Federal State to ministries of education, family, and health. (2) We conducted semi-structured interviews with individuals involved in decision-making regarding school measures in two Federal States, and (3) we undertook semi-structured interviews with members of the guideline panel. The content of response letters in component 1 was analysed descriptively; data for components 2 and 3 were analysed using deductive-inductive thematic qualitative content analysis according to Kuckartz. Results Responses to the Freedom of Information Act inquiries showed that the guideline was recognised as a relevant source of information by ministries of education in nine out of 16 Federal States and used as a reference to check existing directives for school measures in five Federal States. All participants (20 interviews) emphasised the value of the guideline given its evidence- and consensus-based development process but also noted limitations in its usability and usefulness, e.g., lack of context-specificity. It was consulted by participants who advised policy-makers (5 interviews) alongside other sources of evidence. Overall, perceptions regarding the guideline’s impact were mixed. Conclusions Our findings suggest that the guideline was relatively well-known in Federal States’ decision-making bodies and that it was considered alongside other forms of evidence in some of these. We suggest that further research to evaluate the impact of public health guidelines on (political) decision-making is warranted. Guideline development processes may need to be adapted to account for the realities of decision-making during public health emergencies and beyond.